2020
DOI: 10.1080/15384101.2020.1807670
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated microRNA-7 inhibits proliferation and tumor angiogenesis and promotes apoptosis of gastric cancer cells via repression of Raf-1

Abstract: Objective: Since the essential involvement of microRNAs (miRNAs) in the development and progression of GC, the study was for the exploration of the value of microRNA-7 (miR-7) in the evaluation of neoadjuvant chemotherapy for gastric cancer (GC) and its effects on apoptosis, proliferation and angiogenesis of GC. Methods: miR-7 expression in serum of GC patients before and after neoadjuvant chemotherapy were detected to explore its role in neoadjuvant chemotherapy of GC. The GC cells were transfected with miR-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In tumour tissue, cell apoptosis was induced by inhibiting angiogenesis, 40 and cardiac fibrosis had a negative correlation with cardiac angiogenesis 36,37 ; in this study, we demonstrated KN-93 suppressed myocardial angiogenesis, thereby cardiomyocyte apoptosis and cardiac fibrosis were all aggravated by KN-93, and the results were consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In tumour tissue, cell apoptosis was induced by inhibiting angiogenesis, 40 and cardiac fibrosis had a negative correlation with cardiac angiogenesis 36,37 ; in this study, we demonstrated KN-93 suppressed myocardial angiogenesis, thereby cardiomyocyte apoptosis and cardiac fibrosis were all aggravated by KN-93, and the results were consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, the cell suspension was delivered by subcutaneous injection into the right axilla lesions of nude mice. The length (L), width (W) and height (H) of the nodule lesions were measured every week and the lesion volumes were calculated according to the following formula [ 15 ]: V = π/6 (L x W x H). On the 84th day after cell inoculation, the mice were euthanized.…”
Section: Methodsmentioning
confidence: 99%
“…miR-7-5p is the mature form of miR-7 and is closely related to the occurrence and development of tumors (34). For example, miR-7 inhibits the ability of gastric cancer cells to divide, migrate and invade, while promoting their apoptosis (35). circRNA circR-7 acts as a miR-7 sponge that inhibits its biological function (36).…”
Section: Biogenesis and Function Of Circrnamentioning
confidence: 99%